The Importance of a Stable Home and Family Environment in the Prevention of Youth Offending in South Africa - Lutya, Thozama Mandisa (International Journal of Criminology and Sociology, 2012)
The importance of a stable home and family environment in the prevention of youth offending in South Africa. This paper aims to present a strategy to prevent youth offending in South Africa. The strategy is motivated by research findings obtained from the study titled “Home and family circumstances of young offenders: A social worker’s view” in 2007. The findings of this study revealed that socio-economic factors; inept parenting and socialisation practices; exposure to inter-parental violence; sibling criminality; negative parent-child relationship; parental response to deviant behaviour of the child as well as the lack of parental interest in the rehabilitation programmes offered to their offending children increases the likelihood of a child partaking in criminal activities. This paper argues that in order to prevent youth offending South Africa should consider the importance of a stable home and family environment in the prevention of youth offending. Firstly, family planning is important. Secondly, parental involvement in a child’s activities is vital to ensure proper supervision and monitoring. Thirdly, in the absence of adequate parenting skills, efficacy and management parenting programmes could help parents learn a conforming manner of rearing their children. Lastly, once they have been caught committing a crime parents ought to take centre stage to ensure that the child’s behavioural transformation takes place.